ECONOMIC AND LEGAL SUPPORT OF ECONOMIC SECURITY OF MODERN RUSSIAN ENTERPRISES - Кахужева, Аида; Понокова, Данная; Тхаркахова, Ирина (SWorldJournal, 2020)
The article is devoted to the features and problems of economic and legal support of economic security of modern Russian enterprises. Problems of economic security have become relevant for all subjects of economic relations, and its provision has become o